الصحراء المزدحمة دعونا نستكشف علم الآثار في قطر - Shaima Sherif (16020527) (2023)
This item is an Illustrated Presentation  produced by UCL Qatar as part of the The Crowded Desert Project, and is part of Crowded Desert School Pack - Arabic collection.  The Illustrated Presentation is for 6 - 11 years age groups. This work was illustrated by Marsya Abdulghani.